2011
DOI: 10.1186/1477-7827-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy in morphine-induced hypogonadic male chronic pain patients

Abstract: BackgroundIn male patients suffering from chronic pain, opioid administration induces severe hypogonadism, leading to impaired physical and psychological conditions such as fatigue, anaemia and depression. Hormone replacement therapy is rarely considered for these hypogonadic patients, notwithstanding the various pharmacological solutions available.MethodsTo treat hypogonadism and to evaluate the consequent endocrine, physical and psychological changes in male chronic pain patients treated with morphine (epidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…Nevertheless, the present observations suggest that testosterone, but not estradiol, is required in the upregulation of peripheral CB1R under inflammatory conditions. A testosterone deficiency has been reported in chronic pain patients, and testosterone replacement therapy is necessary for satisfactory pain control [3]. Our data suggest that testosterone may be involved in maintaining endogenous antinociceptive systems such as CBR in chronic pain conditions and that effective treatment strategies targeting peripheral CB1R should consider the hormonal status of patients.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, the present observations suggest that testosterone, but not estradiol, is required in the upregulation of peripheral CB1R under inflammatory conditions. A testosterone deficiency has been reported in chronic pain patients, and testosterone replacement therapy is necessary for satisfactory pain control [3]. Our data suggest that testosterone may be involved in maintaining endogenous antinociceptive systems such as CBR in chronic pain conditions and that effective treatment strategies targeting peripheral CB1R should consider the hormonal status of patients.…”
Section: Discussionmentioning
confidence: 69%
“…Epidemiological data show that testosterone levels decline with normal aging (Harman et al, 2001; Feldman et al, 2002), which could lead to reduced opioid efficacy. Recent clinical studies provide compelling evidence that testosterone therapy enhances pain management in elderly men and hypogonadic chronic pain patients (Aloisi et al, 2011; Dedov et al, 2011; Tan et al, 2013). Clinically, low testosterone levels have been linked to various disease states such as diabetes and ischemic heart disease (Barrett-Connor and Khaw, 1988; Barrett-Connor, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 16 men with OPIAD who completed 24 weeks of treatment with testosterone patch therapy experienced improvements in mood/depression and sexual function outcomes [12]. More recently, a study of 17 men with OPIAD and who were receiving epidural morphine for chronic noncancer pain found that TRT (testosterone gel) for up to 12 months was associated with improved sexual function [29]. However, these studies had a limited number of patients, and because they did not include any patients who were not opioid users, potential differences in outcomes between opioid users and nonusers could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%